An Adaptive Finite Element PML Method for the Acoustic-Elastic Interaction in Three Dimensions (Communications in Computational Physics, 2017)
Consider the scattering of a time-harmonic acoustic incident wave by abounded, penetrable, and isotropic elastic solid, which is immersed in a homogeneouscompressible air or fluid. The paper concerns the numerical solution for such anacoustic-elastic interaction problem in three dimensions. An exact transparent boundarycondition (TBC) is developed to reduce the problem equivalently into a boundaryvalue problem in a bounded domain. The perfectly matched layer (PML) techniqueis adopted to truncate the unbounded physical domain into a bounded computationaldomain. The well-posedness and exponential convergence of the solution are establishedfor the truncated PML problem by using a PML equivalent TBC. An a posteriorierror estimate based adaptive finite element method is developed to solve the scatteringproblem. Numerical experiments are included to demonstrate the competitivebehavior of the proposed method.